Perinatal Outcomes in Pregnant Women Users of Illegal Drugs - Tenilson Amaral Oliveira; Ana Aparecida Sanches Bersusa; Tatiana Fiorelli dos Santos; Márcia Maria Auxiliadora de Aquino; Corintio Mariani Neto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Objective The purpose of this study was to evaluate the perinatal outcomes in pregnant women who use illicit drugs. Methods A retrospective observational study of patients who, at the time of delivery, were sent to or who spontaneously sought a public maternity hospital in the eastern area of São Paulo city. We compared the perinatal outcomes of two distinct groups of pregnant women - illicit drugs users and non-users - that gave birth in the same period and analyzed the obstetric and neonatal variables. We used Student's t-test to calculate the averages among the groups, and the Chi-square test or Fisher's exact test to compare categorical data from each group. Results We analyzed 166 women (83 users and 83 non-users) in both groups with a mean of age of 26 years. Ninety-five percent of the drug users would use crack or pure cocaine alone or associated with other psychoactive substances during pregnancy. Approximately half of the users group made no prenatal visit, compared with 2.4% in the non-users group (p < 0.001). Low birth weight (2,620 g versus 3,333 g on average, p < 0.001) and maternal syphilis (15.7% versus 0%, p < 0.001) were associated with the use of these illicit drugs. Conclusions The use of illicit drugs, mainly crack cocaine, represents an important perinatal risk. Any medical intervention in this population should combine adherence to prenatal care with strategies for reducing maternal exposure to illicit drugs.